Phasing Out Energy Subsidies in Indonesia - Mourougane, Annabelle (OECD Publishing, 2010)
The oil price hike in 2007-08 underlined the vulnerability of Indonesia's energy subsidy policy to oil price volatility. In addition to entailing significant economic and environmental costs, energy subsidies put pressure on the public budget and benefit mostly rich households. Phasing them out would benefit both the economy and the environment. At the same time, past experience in Indonesia and elsewhere suggests that such a reform is likely to face stiff opposition and will therefore need to be carefully designed and communicated. Compensation in the form of targeted cash transfers will help to shield low-income households from attendant rise in energy prices. This Working Paper relates to the 2010 OECD Economic Review of Indonesia (www.oecd.org/eco/surveys/Indonesia)
Keywords: Economics; Indonesia